Tinjauan Yuridis atas Kebijakan Outsourcing di Indonesia dan Implikasinya terhadap Kesejahteraan Pekerja - Al Fath; Nada Syifa Nurulhuda; Virna Amalia Nur Permata (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The practice of labor deployment by third-party companies is a common occurrence in Indonesia. However, the paradigm surrounding this labor deployment remains legally ambiguous for some members of the public, which affects the welfare of the workers. This ambiguity prompted the author to conduct a study focusing on the juridical review of outsourcing policies and their implications on worker welfare. Based on the author's research, it was found that the general regulations governing labor deployment or outsourcing issues are Law No. 13 of 2003 on Manpower, Law No. 11 of 2020 on Job Creation, and Minister of Manpower Regulation No. 19 of 2012. A common issue faced is the lack of stringent legal oversight. Additionally, outsourced workers often face injustice concerning wages, benefits, and job instability.